Large eddy simulation modelling for transesterification of waste vegetable oil - Mohiuddin, A. K. M.; Adeyemi, Nabeel A. (2014)
This paper provides the detailed information involved in the numerical simulation of transesterification of waste vegetable oil (WVO). The main objective of this work is to perform mixing study based on large eddy simulation particle image Velocimetry (LES-PIV) which resolved the turbulent scale. Reynolds stress model (RSM) was subsequently used to validate the result using a multiple reference frame (MRF) approach for the impeller-vessel geometry. Experimental FAME yield and liquid velocities were found to be dependent on stirrer speeds, impeller bottom distance and bulk flow pattern. Thermodynamic properties of the reaction components were incorporated as user defined function (UDF) for the mixing models. FAME yield were predicted in terms of species concentration and compared fairly well with experimental condition for 1 and 2-L STR, where yield from the numerical model varied by about 18 and 23 % for 1 and 2-L STR respectively. The characteristic time scales were used to show the relevant mixing scale to describe the process.